2020
DOI: 10.1007/s13181-020-00789-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Transgender Patient Cases Managed by a Toxicologist: an Analysis of the Toxicology Investigator’s Consortium (ToxIC) Registry: January 2017–June 2019

Abstract: Introduction The Toxicology Investigators Consortium (ToxIC) database, created in 2010 by the American College of Medical Toxicology (ACMT), compiles data recorded by medical toxicologists. In January 2017, the data field for transgender (and if transgender, male-to-female or female-to-male) was added to the ToxIC form. Little is known regarding trends in poisonings among transgender patients. We sought to review consultations managed by a bedside toxicologist and provide descriptive data in trends among types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 21 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…One such example of this is the ToxIC database, which did not add the term transgender until 2017. 23 Furthermore, we are limited by the lack of standardization in data collection when it comes to TGD individuals.…”
Section: Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…One such example of this is the ToxIC database, which did not add the term transgender until 2017. 23 Furthermore, we are limited by the lack of standardization in data collection when it comes to TGD individuals.…”
Section: Limitationsmentioning
confidence: 99%
“…One such example of this is the study by Surmaitis et al 23 that looked at toxicology consults in transgender patients. They found that the most common reason for the encounter was intentional self-harm.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transgender persons also have an increased use of illicit substances and nonmedical prescription drug use compared with the US population,3 with potential reasons including coping mechanisms for minority stress 1. One recent analysis of transgender cases managed by a toxicologist showed that the most common primary encounter reason (for either an inpatient or an outpatient toxicology consult) was for intentional use for self-harm 15…”
mentioning
confidence: 99%